2017
DOI: 10.1007/s10616-017-0124-1
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic tumor suppression by a Perilla frutescens-derived methoxyflavanone and anti-cancer tyrosine kinase inhibitors in A549 human lung adenocarcinoma

Abstract: Anti-cancer tyrosine kinase inhibitors (TKIs) are effective in many types of cancers including non-small cell lung cancer, while appearance of TKI-resistant tumors suggests a need for the development of their potentiation strategies. We have previously shown that a methoxyflavanone derivative from the Asian medicinal herb Perilla frutescens (Perilla-derived methoxyflavanone; PDMF) shows a prominent anti-tumor activity against A549 human lung adenocarcinoma. Here we show that PDMF and anti-cancer TKIs (nilotini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Dasatinib, a tyrosine kinase inhibitor, has been approved for first-line treatment of chronic myelogenous leukemia [12]. Various ongoing studies are evaluating the effectiveness of dasatinib in different cancers [13][14][15][16], but the mechanisms underlying the effect of dasatinib on GC progression are not yet clear. Therefore, in this study, we analyzed how dasatinib suppresses the growth of GC cells and interacts with other chemotherapeutic drugs.…”
mentioning
confidence: 99%
“…Dasatinib, a tyrosine kinase inhibitor, has been approved for first-line treatment of chronic myelogenous leukemia [12]. Various ongoing studies are evaluating the effectiveness of dasatinib in different cancers [13][14][15][16], but the mechanisms underlying the effect of dasatinib on GC progression are not yet clear. Therefore, in this study, we analyzed how dasatinib suppresses the growth of GC cells and interacts with other chemotherapeutic drugs.…”
mentioning
confidence: 99%
“…Previous studies have reported that PLE has anti-oxidative, anti-inflammatory, and antitumor effects [ 2 7 ]. Several studies have revealed the presence of anthocyanins, flavonoids, and phenolic acids in P. frutescens [ 3 , 8 11 ]. In addition, recent studies suggest that various compounds in PLE have anticancer activities.…”
Section: Discussionmentioning
confidence: 99%
“…The synergistic anti-tumor effect was fulfilled by induction of cell cycle arrest at both G2/M and G1 phases. 102 The effects of PLE on two cancer cell lines, namely, HCT116 and H1299 (a colorectal cancer cell line and a LC cell line, respectively) were investigated. Treatment of these cells with PLE, dose-dependently inhibited cancer cells proliferation by 52-92% and completely abolished the colony formation in soft agar.…”
Section: Perilla Frutescensmentioning
confidence: 99%